074 Who thinks teenagers are a problem? Cross-sectional evidence on perceptions of anti-social behaviour, health and place. (16th November 2010) - Egan, M
Abstract : Objective: Perceptions of anti-social behaviour (PASB) are a policy priority and linked to numerous social harms including experience of ASB. National survey findings have associated PASB with individual and area level deprivation, potentially adding to the multiple disadvantages said to contribute to health inequalities. We ask whether PASB have independent associations with ill health compared to other individual and neighbourhood characteristics for residents of deprived inner-city neighbourhoods (Glasgow, UK). Methods: Randomly selected adult residents of 14 deprived neighbourhoods answered face-to-face structured questionnaires. A stepwise logistic regression (clustered by area) produced a multivariate model including self-rated measures of health, GP visits, psychosocial wellbeing, homes, neighbourhoods, and demographic characteristics. Perceiving teenagers hanging around to be a serious neighbourhood problem was the dependent variable. Results: 6008 adults participated (50% response). Regular annual GP visits (>6) were associated with PASB (OR 1.29; p=0.011; 95% CI 1.06 to 1.56), as was GP visits (>0) for mental health reasons (OR 1.44; p=0.020; 95% CI 1.06 to 1.96). PASB was inversely associated with self/collective efficacy (OR 1.25; p=0.028; 95% CI 1.02 to 1.53); self-esteem (OR 1.56; p<0.001; 95% CI 1.30 to 1.87); trust (OR 1.53; p<0.001; 95% CI 1.19 to 1.96); feeling safe (OR 1.71; p<0.001; 95% CI 1.41 to 2.06); social support (OR 1.94; p<0.001; 95% CI 1.45 to 2.59); age (OR 2.33; p<0.001; 95% CI 1.56 to 3.50); living with children (OR 1.20; p=0.001; 95% CI 1.06 to 1.37) home condition (OR 1.31; p=0.006; 95% CI 1.08 to 1.58); home security (OR 1.31; p=0.042; 95% CI 1.01 to 1.71); neighbourhood exposure (OR 1.60; p=0.015; 95% CI 1.09 to 2.34); rating of police (OR 1.65; p<0.001; 95% CI 1.34 to 2.02). PASB was positively associated with fuel poverty (OR 1.43; p=0.011; 95% CI 1.09 to 1.87); neighbour contacts (OR 1.60; p=0.005; 95% CI 1.10 to 1.71); neighbourhood decline (OR 2.42; p<0.001; 95% CI 1.84 to 3.89); noisy environment (OR 1.23; p=0.042; 95% CI 1.01 to 1.50), and area type (OR 1.59; p<0.001; 95% CI 1.33 to 1.91). General health and longstanding illness were not associated with PASB after adjustment (p>0.05). Conclusion: National surveys link PASB to socio-economic status but the deprived communities we surveyed have relatively little socio-economic variance. Therefore other characteristics like GP use (particularly for mental health reasons) and psychosocial wellbeing become more important in explaining PASB. Future longitudinal research is planned to explore causation—for example, do GP users worry about teenagers because illness encourages feelings of vulnerability—or does worrying about neighbourhood problems exacerbate ill health? Current findings are consistent with the view that addressing PASB be included in strategies to address health inequalities.